An Analysis of English Teachers’ Abilities and Difficulties in Designing ''Modul Ajar'' in the Merdeka Curriculum at SMAN 2 Batang Anai - Winda, Srie Novita; Tiarina, Yuli (Journal of English Language Teaching, 2024)
This research was conducted to investigate the abilities and the difficulties faced by English teachers in designing Modul Ajar in the Merdeka curriculum at SMAN 2 Batang Anai. This research used qualitative research using the case study method with documentation and in-depth interview instruments employed in this study. The participants involved were two English teachers who teaching at the 10th and 11th grade. The result showed that the abilities of English teachers were in sufficient category and poor category with scores of 70 and 60 respectively. Meanwhile, the difficulties faced by English teachers include: a) difficulty in determining an effective learning approach; b) difficulty choosing the right learning method; c) difficulty in creating learning materials that are interesting for all students and appropriate to learning methods; d) difficulty in designing learning steps to fit the available time allocation; e) difficulty in choosing the right learning strategy to suit the learning steps and time allocation; f) difficulty in relating the material to everyday life or real-life contexts in trigger questions; g) difficulty adjusting learning activities to the time in class; h) difficulty in facilitating or providing material that meets all students' needs; i) difficulty in creating student worksheets and assessment instruments due to limited time. Through this research, it is hoped that the findings can help English teachers find out their abilities and difficulties they face.